OPERATIONALIZATION OF EXCELLENT SERVICE: OPERATIONALIZATION OF EXCELLENT SERVICE - Fitriani, Aida (FOKUS : Publikasi Ilmiah untuk Mahasiswa, Staf Pengajar dan Alumni Universitas Kapuas Sintang., 2025)
Technically, the Puskesmas is tasked with providing services that include treatment, prevention, health improvement, and health recovery services aimed at all residents in its working area. The research objectives can be analyzed and described the principles and concepts of Excellent Service at Puskesmas by conducting Descriptive research. Data collection techniques used are, indepth interviews with purposive informants, observation and documentation studies. The principles and concepts of Excellent Service at Puskesmas are prioritizing the community/patient, an effective system, serving with conscience, making continuous improvements and empowering the community/patient. The implementation of Excellent Service at the Health Center is a renewal of service design through several activity steps, namely determining the type of service, appreciating community/patient activities and designing service processes. It is recommended that Puskesmas apply the Health Service Process Model as a whole, especially formulating goals and objectives as guidance in the implementation of health service policies provided.